HLA-VBSeq: accurate HLA typing at full resolution from whole-genome sequencing data. (December 2015) - Nariai, Naoki; Kojima, Kaname; Saito, Sakae; Mimori, Takahiro; Sato, Yukuto; Kawai, Yosuke; Yamaguchi-Kabata, Yumi; Yasuda, Jun; Nagasaki, Masao
Abstract Background Human leucocyte antigen (HLA) genes play an important role in determining the outcome of organ transplantation and are linked to many human diseases. Because of the diversity and polymorphisms of HLA loci, HLA typing at high resolution is challenging even with whole-genome sequencing data. Results We have developed a computational tool, HLA-VBSeq, to estimate the most probable HLA alleles at full (8-digit) resolution from whole-genome sequence data. HLA-VBSeq simultaneously optimizes read alignments to HLA allele sequences and abundance of reads on HLA alleles by variational Bayesian inference. We show the effectiveness of the proposed method over other methods through the analysis of predicting HLA types for HLA class I (HLA-A, -B and -C) and class II (HLA-DQA1, -DQB1 and -DRB1) loci from the simulation data of various depth of coverage, and real sequencing data of human trio samples. Conclusions HLA-VBSeq is an efficient and accurate HLA typing method using high-throughput sequencing data without the need of primer design for HLA loci. Moreover, it does not assume any prior knowledge about HLA allele frequencies, and hence HLA-VBSeq is broadly applicable to human samples obtained from a genetically diverse population.